Threshold concepts about online pedagogy for novice online teachers in higher education. Issue 7 (10th November 2019) - Kilgour, Peter; Reynaud, Daniel; Northcote, Maria; McLoughlin, Catherine; Gosselin, Kevin P.
ABSTRACT: The use of threshold concepts to define key points of curricula is a relatively recent development in educational research. Threshold concepts represent crucial stages of learning, the acquisition of which enables learners to progress from one level of achievement to another. In this context, the learner is described as passing through an unsettling liminal space in which they may encounter troublesome knowledge and experience uncertainty or anxiety. When applied to online pedagogy in higher education contexts, academic staff become the learners as they extend their on-campus teaching knowledge into the online realm. In this setting, the identification of threshold concepts has the potential to inform the content of professional development (PD) programmes for novice online teachers. Because little research has yet been reported on threshold concepts associated with online teaching, this study identified these threshold concepts and investigated their specific nature. Funded by an Office for Learning and Teaching Australia Grant, the project employed a mixed-methods research approach. A mixture of qualitative and quantitative data was gathered from responses to questionnaires and reflective journal entries provided by university educators who were teaching in online contexts. Also, experts in the fields of PD, online teaching and threshold concepts were consulted using a modified Delphi technique that incorporated two rounds of surveys. Results of this study are discussed in association with potential applications to PD design for novice online educators, informed by the most fundamental learning experiences encountered by their more experienced colleagues.